Gender equality in the labour market: Attitudes to women's work - Sylke Viola Schnepf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2006)
The analysis of economic factors usually applied for examining gender inequality in the labour market suggests that former post communist countries in Central and Eastern Europe have reached similarly high standards of gender equality compared to Western European countries. This paper aims at comparing attitudes to women's work between transition and OECD countries highlighting the explanatory power of societal norms. The analysis of attitudes, their determinants and their change in regions and countries is based on mainly two waves (1994 and 1998) of the International Social Survey Program (ISSP). These data reveal that a strikingly higher share of people in the East than in the West agrees with traditional values on women's work. The large homogeneity in patriarchal values of Eastern European people with differing socio-economic background explains these regional differences. The East-West gap in traditional value orientations is likely to widen given that liberal values spread faster in OECD than in transition countries.
Keywords: 330